A STUDY ON THE EFFICACY OF ISLAMIC PAWN BROKING SERVICES IN FULFILLING SOCIO –ECONOMIC NEEDS: A CASE OF TWO CITIES-KUANTAN AND KUALA TERENGGANU IN MALAYSIA - Mohd Noar, Nor; Islam, Mohd (PEOPLE: International Journal of Social Sciences, 2015)
In this paper we aim to examine the effectiveness of Al-Rahnu (Islamic pawn broking) services in fulfilling and enhancing socio-economic needs of its users as an alternative source of managing short term cash flow problem. To achieve our objectives we conducted a survey in two cities of Malaysia: Kuantan and Kuala Terengganu in the states of Pahang and Terengganu respectively. A sample of 128 users of Ar-Rahnu services were used to collect data through distributing a semi-structured questionnaire. The results were analyzed via the cross tabulation using excel spreadsheets. The findings from this study revealed that the community, especially the Malay ethnicity found Al-Rahnu services effective in fulfilling their needs of getting access to small short term loans with fast and hassle freeway and hence making them loyal to Al-Rahnu services. This implies that the Ar-rahnu services are well accepted as a better mean to ease short term financial difficulties and hence able to empower socio-economic needs of the people. The fulfillment of needs are derived from two main components of Al-Rahnu survey questions i.e. the loan tenure and the loan sufficiency.